Species Occurrence and Seasonal Variation of Malaria Vectors in Hadiya Zone, Ethiopia. - Assemie, Anmut; Mulu, Dasash; Mekuriaw, Eyerus; Muluken, Workineh; Azmat, Syed Khurram (BioMed Research International, 2026)
Environmental change can alter the species occurrence and seasonal distribution of malaria vectors to higher altitudes and latitudes. Highlands remain dynamic due to factors that favor their growth and development. Invasive species have proliferated into new ecological niches, increased. These studies aimed to determine the species occurrence and seasonal variation of malaria vectors in the selected study area. Entomological surveys were conducted in different types of larval habitats from October 2023 up to June 2024 within four purposively selected study villages. The species were morphologically identified using a stereomicroscope, and then data was analyzed using R version 4.3.1 (2023‐06‐16 ucrt) statistical analysis software. A total of 721 malaria vector larvae were collected, representing Anopheles gambiae s.l., An. funestus s.l., An. coustani, and An. pharoensis. An. gambiae s.l. was the dominant species, accounting for 43.82% (n = 316) of all collections, while An. pharoensis was the least abundant (7.9%, n = 57). Spatial variation was observed, with Shemo Boyo recording the highest number of larvae (45.50%, n = 328), whereas Kemecho Borara had the lowest (9.57%, n = 69). Among the habitat types, ditches had the highest mean larval density (2.61 larvae per sample), followed by swamps (1.5) and riverbeds (0.8), whereas water pans had the lowest density (0.14). Overall mean larval density was 1.11 larvae per sample, and larval abundance significantly differed across habitat categories (f (3,647) = 4.005, p = 0.012). These findings indicate that An. gambiae s.l. is the predominant malaria vector in the area and likely plays a primary role in local transmission. Further studies on spatial mapping, physicochemical characterization, habitat preference, and isolation of malaria parasites are recommended to guide targeted larval source management and reduce the burden of mosquito‐borne diseases.